(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
“You can’t dismantle the master’s house with the master’s tool.”Dalit literature is a post-colonial upsurge against the hegemony of oppression. It depicts the bitter truth of the caste based social fabric of Independent India and the unconquerable challenges faced by the dalits. Its main objective is to raise the voice of protest and make the oppressors heard the new voice of justice and equality. But when the oppressed tried to give vent to their long muted anguish and pain through literature, it was not paid heed to. Their articulation was not considered worthy to be read as literature because it doesn’t fit to their normative aesthetics. Audre Lorde rightly said “you can’t dismantle the master’s house with the master’s tool.” Dalit writers argue that literary standards change with change of culture. Also counter the theory that someone’s writing will be called literature only when ‘our’ literary standards approve, it is a sign of literary dictatorship. Further, dalit critics propose to include and recognize ‘revolt’ as tenth, ‘cry’ should be accepted as the eleventh ‘rasa’, to complete the ‘rasa’ theory. Because, Dalit literature is not about beauty or pleasure, it is about the sufferings and revolts of the Dalits. So, its aesthetics can’t be based on the principles of a normative aesthetics of literature where privileged derive pleasure from beauty. So, it is imperative to develop the separate aesthetic to assess the dalit literature. This paper is an attempt to throw light on why abrogation of normative aesthetics is necessary and why there is a dire need to have alternate narrative to appraise dalit literature.